Optical Coherence Tomography Angiography of Combined Central Retinal Artery and Vein Occlusion - Shuo-chieh Wu; Victor M. Villegas; Jaclyn L. Kovach (Case Reports in Ophthalmological Medicine)
Optical coherence tomography angiography (OCTA) is a new, noninvasive technology that enables detailed evaluation of flow in the retinal and choroidal vasculature. The authors believe this to be the first report to describe the optical coherence tomography angiography findings associated with combined central retinal artery occlusion (CRAO) and central retinal vein occlusion (CRVO).